From declaration to real protection: Biodiversity and local participation in the management of four protected areas in Nicaragua - Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2010)
Genuine protection of declared protected areas depends on an explicit focus on how to manage actors and their mutual relations, i.e. how to regulate their activities, encouraging some and restricting others, rather than on a focus on how to manage an area as a territory. This is one of the conclusions resulting from comparative research undertaken in collaboration between Nicaraguan and Danish researchers on local participation, plant biodiversity and local knowledge on plants in the management of four Nicaragua protected areas. The research project has been financed as part of the Danish environmental sector support programme to Nicaragua and has been coordinated by Helle Munk Ravnborg at DIIS.
Keywords: 300; Schutzgebiet; Biodiversität; Bürgerbeteiligung; Nicaragua